Meta-analysis of tick-borne and other pathogens: Co-infection or co-detection? That is the question - Stefania Porcelli; Pierre Lucien Deshuillers; Sara Moutailler; Anne-Claire Lagrée (Current Research in Parasitology and Vector-Borne Diseases)
This literature-based review aims to distinguish studies describing co-infection with tick-borne pathogens from those describing co-detection or co-exposure scenarios. The review analyzed 426 papers and identified only 20 with direct evidence of co-infection in humans and animals, highlighting the need for accurate terminology and proposing definitions for co-infection, co-exposure and co-detection. Current diagnostic methods - including serology and molecular techniques - have limitations in accurately identifying real co-infections, often leading to misinterpretation. The review highlights the importance of developing laboratory models to better understand tick-borne pathogen interactions, and advocates improved diagnostic strategies for tick screening by testing their RNA for co-infections. Moreover, the establishment of additional animal models for pathogen co-infection will help develop our understanding of selection pressures for various traits of tick-borne pathogens (such as virulence and transmissibility) over time. This comprehensive analysis provides insights into the complexity of tick-borne pathogen co-infections and calls for precise diagnostic terms to improve the clarity and effectiveness of future research.